Mindfulness Training untuk Menjadi Guru Bahagia di Sekolah Dasar Islam Mutiara Al-Madani Kota Sungai Penuh - Hengki Yandri; Samsul Bahry Harahap; Syamsarina; Dosi Juliawati (Fakultas Ushuluddin, Adab, dan Dakwah, 2022)
Being a teacher in elementary school is not easy, in teaching sometimes teachers are faced with student behavior that irritates, so the teacher's emotions become unstable. Thus, the purpose of This Mindfulness Training helps teachers become someone who remains happy with all the behaviors that students display at school and even unpleasant events that occur in schools. Mindfulness Training activities are carried out in the form of training activities that allow teachers to directly practice in dealing with situations that make teachers uncomfortable. The participants of the training activity were 30 teachers of Mutiara Al-Madani Islamic Elementary School, Sungai Penuh City. The results of the Mindfulness Training that have been carried out show that 80% of teachers understand how to manage emotions so that they can enjoy being happy teachers. Foundation administrators should provide similar training to increase the insight, knowledge, and skills of teachers in teaching and dealing with all situations that occur in schools.